Female Circumcision on a Medical Perspective and Islamic Law - Amin, Ibnu; Lendrawati, Lendrawati (Analisis: Jurnal Studi Keislaman, 2022)
The practice of female circumcision existed long before Islam came in the 16th century BC in South Africa, Southwest Asia, Judaism, Arabia and Egypt. Islamic teachings legalize obligatory circumcision for men and honor for women. However, in a medical review, female circumcision is prohibited on the grounds that it violates human rights and harms women. The emergence of this difference is motivated by a generalized definition and practice of circumcision. This research is a library research using descriptive method and drawing conclusions using deductive thinking. The research found that circumcision or Female Genitical Mutilation (FGM) in the medical formulation as recommended by WHO is a practice that violates Human Rights (HAM) and harms women's rights practiced in more than 30 countries with five types: eliminating, cutting, stabbing, sewing and damage the female organs. The practice of female circumcision (khifad) in Islam only scratches the upper female genital skin in the form of a cock's comb, the status of female circumcision according to Islam refering to most scholars is "sunnah" which is a glory. Nobility is meant from two sides, compliance with the Shari'a and respect in social life carried by a circumcised woman according to the qaidah al-'adat al-muhkam.